Algo Descabellado (2024)
This project considers family memory from an intimate or personal space (the house), in this context A bond is created between mother and daughter through the ritual that is established in the action of combing, in which the hair is untangled, braid, gives shape not only to the hair, but to the narratives that seem to keep these same actions from the word. That is to say, they are as a whole actions that are drawn and thus give meaning to this language. In other words, The drawing can account for or materialize this ritual.